2018
DOI: 10.3390/ijerph15112470
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Motor Competence in Association with Sedentary Behavior and Physical Activity in 7- to 11-Year-Old Children

Abstract: Children’s motor competence (MC) has declined in the past decades, while sedentary behavior (SB) has increased. This study examined the association between MC and physical activity (PA) levels among primary schoolchildren. Demographics, body height and weight, MC (Athletic Skills Track), and PA levels (ActiGraph, GT3X+) were assessed among 595 children (291 boys, mean age = 9.1 years, SD = 1.1). MC was standardized into five categories: from very low to very high. PA levels were classified into SB, light PA (L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
1
19
0
1
Order By: Relevance
“…More recently, a reduction of physical activity (i.e., 2.30 h/week) has been found in prior research regarding confined children and adolescents due to Covid-19 (30); such values were higher than those found in the present study, which observed a difference of 1.40 h/week in respect to previous confinement levels. Differences between the two studies concerning physical activity could be attributed to different sample characteristics; for instance, children from higher socioeconomic backgrounds have shown higher levels of physical activity, whereas the context of confinement might influence physical activity levels (e.g., more time confined or experiencing stricter confinement can modify ordinary levels of physical activity) (28)(29)(30)(31)(32). Closure of schools during both strict and relaxed confinement might play a key role in this found reduction since schools, and, particularly physical education classes provide an adequate environment to promote active behaviors among children and adolescents (33)(34)(35).…”
Section: Physical Activitymentioning
confidence: 99%
“…More recently, a reduction of physical activity (i.e., 2.30 h/week) has been found in prior research regarding confined children and adolescents due to Covid-19 (30); such values were higher than those found in the present study, which observed a difference of 1.40 h/week in respect to previous confinement levels. Differences between the two studies concerning physical activity could be attributed to different sample characteristics; for instance, children from higher socioeconomic backgrounds have shown higher levels of physical activity, whereas the context of confinement might influence physical activity levels (e.g., more time confined or experiencing stricter confinement can modify ordinary levels of physical activity) (28)(29)(30)(31)(32). Closure of schools during both strict and relaxed confinement might play a key role in this found reduction since schools, and, particularly physical education classes provide an adequate environment to promote active behaviors among children and adolescents (33)(34)(35).…”
Section: Physical Activitymentioning
confidence: 99%
“…Another strength of this study is that PA was objectively measured and that the compliance of the participants was high, i.e., the average mean accelerometer wear time was over 13 h per day during waking hours for four school days. A limitation of this study was the overrepresentation of grade-6 children with low MC compared to grade-4 children, while in the whole research population, the number of children in both groups was equally distributed [12]. Also, the study only focused on weekday patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Data used in the current study derived from the SALTO (Dutch acronym for Stimulating an Active Lifestyle Through Physical Education) study [12]. This study was conducted on ten primary schools in the south of the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research projects indicate that excessive time without PA might play a negative role in children’s lives, especially in combination with screen activities [ 24 , 25 , 26 ]. According to terminology consensus, such behavior can be called “sedentary behavior” or “stationary behavior” [ 10 ].…”
Section: Introductionmentioning
confidence: 99%